Development of a method for ranking factors that influence the maturity of project quality management processes - Lazko, Iryna (Eastern-European Journal of Enterprise Technologies, 2018)
According to the results of the theoretical analysis of well-known and widely practically applied standards of quality management and project management, as well as models of maturity assessment of processes, 13 key risk-dominant factors influencing the maturity of project quality management processes have been identified. A methodology of ranking risk-dominant factors, which highly influence the organizational maturity of quality management processes in projects, has been developed. The basis of the developed methodology is the expert method. A distinctive feature of the methodology when it is implemented is to obtain a nomenclature of ranked key risk-dominant factors, taking into account the expertise of experts. This result is achieved through the involvement of two target groups, «Process Implementers» and «Consumers of the Process Results and Stakeholders», for peer review. A systematic scientifically-based ranking of risk-dominant factors in accordance with the proposed methodology contributes to the objective assessment of the potential of quality management processes in projects. In addition, it will increase the likelihood of obtaining expected results of processes and will determine the priority directions of growth and organizational changes of processes to achieve the target levels of maturity. The proposed methodology can be implemented in the processes of certification, self-assessment and auditing in a QMS. The practical testing of the proposed methodology was carried out using the example of the «Project Launch» process. According to the results of the expert evaluation of the «Process Implementers», it has been established that the factor «The degree of documenting the process» and, to a lesser extent, the «The degree of applicability of the process evaluation results for its improvement» is influenced to a greater extent by the maturity of the investigated process. According to the results of the expert evaluation «Consumers of the Process Results and Stakeholders», the following has been established. To a greater extent, the maturity of the investigated process is influenced by the factor «The degree of the possibility of integrating the process with other internal and external processes. «To a lesser extent, the factor is «Behaviour of the process implementers». There is a high degree of consistency between expert assessments within each group and a significant connection between the assessments of the two groups of experts.